9 Stat. at Large of Pa. 336-37, ch. 833, § 9 (1903) - (:unkn) unknown (My University, 1779)
That if any person within this commonwealth shall challenge the person of another to fight at sword, pistol, rapier or other dangerous weapon, such person so challenging shall forfeit and pay for every such offense (being lawfully convicted by the testimony of one or more credible witnesses, or by the confession of the party offending,) the sum of five hundred pounds, or suffer twelve months imprisonment without bail or mainprise
Keywords: DUELING